Industry of Anonymity: Inside the Business of Cybercrime - Lusthaus, Jonathan (Harvard University Press, 2018)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- 1. Introduction -- 2. From Lone Wolves to Industrialization -- 3. Making Sense of the Cybercrime Industry -- 4. Nicknames and Identity -- 5. How Cybercriminals Cooperate Online -- 6. The Offline Dimension -- 7. Cybercrime, Organized Crime, and Governance -- 8. Conclusion -- Appendix 1: List of Participants -- Appendix 2: Data and Methods -- Notes -- Acknowledgments -- Index